Embroidered wearable Antenna-based sensor for Real-Time breath monitoring. (31st May 2022) - El Gharbi, Mariam; Fernández-García, Raúl; Gil, Ignacio
Highlights: Design and validation of a novel fully embroidered meander dipole antenna-based sensor integrated into a commercially available T-Shirt for real-time breathing monitoring. The measurements were carried out to monitor the breathing of a female volunteer for various positions (standing and sitting) with different breathing patterns: eupnea (normal respiration), apnea (absence of breathing), hypopnea (shaloow breathing) and hyperpnea (deep breathing). The considered antenna-based sensor has the advantages of combining a wearability, compact size, consistent performance and no fabrication complexities. Comparison with recent works. Abstract: In this paper we present the design and the validation of a novel fully embroidered meander dipole antenna-based sensor integrated into a commercially available T-shirt for real-time breathing monitoring using the technique based on chest well movement analysis. The embroidered antenna-based sensor is made of a silver-coated nylon thread. The proposed antenna-sensor is integrated into a cotton T-shirt and placed on the middle of the human chest. The breathing antenna-based sensor was designed to operate at 2.4 GHz. The sensing mechanism of the system is based on the resonant frequency shift of the meander dipole antenna-sensor induced by the chest expansion and the displacement of the air volume in the lungs during breathing. The resonant frequency shift was continuously measured using a Vector Network Analyzer (VNA) to a remote PC via LAN interface in real-time. A program was developed via Matlab to collect respiration data information using a PC host via LAN interface to be able to transfer data with instrumentation over TCP/IP. The measurements were carried out to monitor the breathing of a female volunteer for various positions (standing and sitting) with different breathing patterns: eupnea (normal respiration), apnea (absence of breathing), hypopnea (shallow breathing) and hyperpnea (deep breathing). The measured resonance frequency shift to 2.98 GHz, 3.2 GHz and 2 GHz for standing position and 2.84 GHz, 2.95 GHz and 2.15 GHz for sitting position, for eupnea, hyperpnea and hypopnea, respectively. The area of the textile sensor is 45 × 4.87 mm2, reducing the surface consumption significatively with regard to other reported breath wearable sensors for health monitoring.